Stem Cell Cytoskeletal Responses to Pulsatile Flow in Heart Valve Tissue Engineering Studies - Castellanos, Glenda; Nasim, Sana; Almora, Denise M.; Rath, Sasmita; Ramaswamy, Sharan (Frontiers in Cardiovascular Medicine, 2018)
Heart valve replacement options remain exceedingly limited for pediatric patients because they cannot accommodate somatic growth. To overcome this shortcoming, heart valve tissue engineering using human bone marrow stem cells (HBMSCs) has been considered a potential solution to the treatment of critical congenital valvular defects. The mechanical environments during in vitro culture are key regulators of progenitor cell fate. Here, we report on alterations in HBMSCs, specifically in their actin cytoskeleton and their nucleus under fluid-induced shear stresses of relevance to heart valves. HBMSCs were seeded in microfluidic channels and were exposed to the following conditions: pulsatile shear stress (PSS), steady shear stress (SS) and no flow controls (n=4/group). Changes to the actin filament structure were monitored and subsequent gene expression was evaluated. A significant increase (p < 0.05) in the number of actin filaments, filament density and angle (between 30° and 84°), and conversely a significant decrease (p < 0.05) in the length of the filaments were observed when the HBMSCs were exposed to PSS for 48 hours compared to SS and no flow conditions. No significant differences in nuclear shape were observed among the groups (p > 0.05). Of particular relevance to valvulogenesis, klf2a, a critical gene in valve development, was significantly expressed only by the PSS group (p < 0.05). We conclude that HBMSCs respond to PSS by alterations to their actin filament structure that are distinct from SS and no flow conditions. These changes coupled with the subsequent gene expression findings suggest that at the cellular level, the immediate effect of PSS is to initiate a unique set of quantifiable cytoskeletal events (increased actin filament number, density and angle, but decrease in filament length) in stem cells, which could be useful in the fine-tuning of in vitro protocols in heart valve tissue engineering.